STRATEGIES TO IMPROVE COTTONSEED OIL COMPOSITION AND REFORMULATE FATTY ACID PROFILE - Khamrakulova Muborak Khakimovna; Saydullaeva R. Dilrabo (European Science Publishing, 2024)
Cottonseed oil is a widely utilized edible oil with significant applications in the food industry. However, its fatty acid composition, characterized by a high content of saturated fats and specific undesirable compounds, necessitates improvements to meet health and nutritional standards. This article explores innovative strategies to enhance the composition of cottonseed oil and reformulate its fatty acid profile. Key approaches include genetic engineering of cottonseed varieties, selective breeding, and advanced processing technologies such as enzymatic interesterification and hydrogenation control. The study also examines the role of biotechnological interventions in reducing gossypol content and increasing unsaturated fatty acid proportions, particularly oleic and linoleic acids. Furthermore, the article highlights the implications of these modifications on oil stability, flavor, and overall health benefits. By integrating cutting-edge research and industrial practices, this study offers actionable insights into producing cottonseed oil with an optimized fatty acid profile, aligning with consumer preferences and health guidelines.
Keywords: Vegetable oil, cholesterol content, functional, genetic resources, cottonseed, fatty acids, genetic resources, global vegetable oil, selection, designer oils.